The impact of the neighborhoods "300 houses" and "Plan VEA" as city builders in urban expansion at the beginning of the seventies in the city of Corrientes (ARQUISUR Revista, 2021)
Social interest housing assumes a significant role in shaping the urban fabric of the city, manifested by the materialization of neighborhood groups carried forward through the operations implemented by credit institutions. The Peronist government between 1946 and 1955, within an important plan of public works positioned the construction of housing of social interest in a relevant place. Its fall in 1955 generated a change in the orientation of social housing policies in the national space. The support to the internal savings systems and the Alliance for Progress characterized the guidelines taken forward. Materialized at the beginning of the 70s, the neighborhoods "Plan VEA" and "300 houses" are located to the south of the central area of ​​the city of Corrientes, with an urban environment that in recent years underwent changes due to the occupation of spaces. free of building. Currently, both neighborhoods are fully integrated into the urban fabric in a sector that in recent years evidenced an important real estate development, accompanied by the extension of urban infrastructure, according to the analysis of the category of demographic evolution and graphic documentation of the sources analyzed.
Keywords: savings, green spaces, periphery, urban plot, urban housing